Pengaruh Online Customer Review Dan Tagline “Gratis Ongkir” Terhadap Keputusan Pembelian - Stiffanny, Nichollin; Adlina, Hafiza (Peneliti.net, 2025)
In this digital era, the development of internet technology has greatly influenced people's lifestyles, especially in shopping which nowadays can easily be done online. Shopee is an e-commerce company that continues to grow and compete to maintain its position in the hearts of the public. Therefore, Shopee needs the right strategy to attract consumer interest and loyalty. This research aims to analyze the influence of online customer reviews and the tagline